ACHIEVING HIGH-QUALITY FOAMING AND WEIGHT REDUCTION IN MICROCELLULAR INJECTION MOLDED POLYCARBONATE USING SUPERCRITICAL CARBON DIOXIDE COMBINED WITH GAS COUNTER PRESSURE - Hendra Agustion, Yogi
Injection molding is a widely used plastic processing method known for producing complex shapes in large quantities, with applications in many industries. Over time, the combination of conventional injection molding and microcellular foaming using supercritical fluid (SCF) as a foaming agent led to the so-called MuCell® process. MuCell® offers benefits such as reductions in product weight, shortening cycle time, minimizing shrinkage and warpage, and eliminating residual stresses. However, application challenges remain, particularly regarding the foaming quality, which is related to the cell size, size distribution, and cell density of the molded parts. This study investigates the impact of CO2 as a gas blowing agent, as well as MuCell® processing parameters, including SCF dosage, melt temperature, mold temperature, and injection speed, on the achievement of smaller cell sizes and higher cell densities, along with weight reduction for polycarbonate (PC) material. Gas counter pressure (GCP), which has been proven to improve the surface and foaming qualities of MuCell® parts, is also used in this research to evaluate its relevant effect on foaming quality. Based on the Taguchi design experiment analysis combined with regression analysis and grey relational analysis (GRA), the results reveal that using CO2 gas in the MuCell® process for PC material with a targeted 35% weight reduction can make microcellular cells down to 40 ?m in size and cell densities up to 3.97 x 106 cells/cm3. A higher SCF dosage was found to be the most significant factor in attaining smaller cell sizes and higher cell densities. The next influence is the reduction in mold and melt temperatures. Injection speed has the least impact. Additionally, using GCP significantly improved the MuCell® molded parts by reducing cell size by 45.41% and increasing cell density by 102.48% compared to parts without GCP. Obviously, higher GCP was the most influential factor, and increased gas holding time also further reduces cell size and increases cell density. Additionally, GCP can enhance the uniformity of cell size distribution, with 92% of the cells being under 40 ?m and an improvement of 156% in cells under 20 ?m compared to parts molded without GCP. However, implementing GCP may require a compromise on the target weight reduction.